Representation of two Contrary States of Human Soul: Songs of Innocence and Experience by William Blake - Jha, Dr. Suprita (International Journal of Humanities and Education Development (IJHED), 2020)
It is difficult to ignore the basic point about William Blake that though chronologically he is an eighteenth-century poet, he is a highly gifted and immensely successful lyric poet. While Blake’s poetry may or may not have the pleasantness of great poetry, it is perhaps true that Blake has no notable predecessors and no followers. He consistently stresses the importance of freedom, as opposed to the tyranny that he feels to be characteristic of the government of his day, and attacks negative moralizing, which he associates with the church, as opposed to a true sense of religion. The Songs of Innocence and of Experience occupy a vital place in the corpus of Blake’s poetical writings. This is so because these Songs are as much the product of Blake’s earlier writings as the pointer to his future writings. The kind of philosophical tone that we encounter in The Songs of Innocence and of Experience is indeed astounding. It is said that Blake looked upon poetry as something that is dictated by spirits, or as the result of inspiration, but he was also aware of the role of the poet to bring out certain truths of human life in front of the people in a symbolic way. There is no doubt about the fact that in the corpus of English Poetry no other poet has got as much success, if equal but certainly not more, as Blake. The present paper is mainly focused on the philosophical appeal and symbolic portrayal of human existence that the Songs of William Blake illustrate to us.